Coordinative interactions between porphyrins and C60, La@C 82, and La2@C80 - Tsuchiya, Takahiro; Rudolf, Marc; Wolfrum, Silke; Radhakrishnan, Shankara Gayathri; Aoyama, Ryo; Yokosawa, Yuya; Oshima, Azusa; Akasaka, Takeshi; Nagase, Shigeru; Guldi, Dirk Michael (Chemistry - A European Journal, 2013)
For the first time, a C derivative (1) and two different lanthanum metallofullerene derivatives, La@CPy (2) and La @CPy (3), that feature a pyridyl group as a coordination site for transition-metal ions have been synthesized and integrated as electron acceptors into coordinative electron-donor/electron-acceptor hybrids. Zinc tetraphenylporphyrin (ZnP) served as an excited-state electron donor in this respect. Our investigations, by means of steady-state and time-resolved photophysical techniques found that electron transfer governs the excited-state deactivation in all of these systems, namely 1/ZnP, 2/ZnP, and 3/ZnP, whereas, in the ground state, notable electronic interactions are lacking. Variation of the electron-accepting fullerene or metallofullerene moieties provides the incentive for fine-tuning the binding constants, the charge-separation kinetics, and the charge-recombination kinetics. To this end, the binding constants, which ranged from log K=3.94-4.38, are dominated by axial coordination, with minor contributions from the orbital overlap of the curved and planar π systems. The charge-separation and charge-recombination kinetics, which are in the order of 10 and 10 s, relate to the reduction potential of the fullerene and metallofullerenes, respectively. Copyright © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.